Making working drawings and mockups of the redesign of the Dayak traditional lamin for the preservation of East Kalimantan's indigenous culture - Nur Husniah Thamrin; Mafazah Noviana (Universitas Muhammadiyah Magelang, 2021)
Culture in East Kalimantan has many varieties that are increasingly disappearing if conservation efforts are not carried out both by the community, agencies/institutions, especially in schools/campuses that are in direct contact with matters of culture. One of the cultures that is currently of concern is the culture of the Dayak Kenyah community in the Pampang cultural village, Samarinda. Besides being a cultural heritage, Pampang village is also an asset for tourism and education for local communities and foreign tourists. The condition of the lamin building which is getting old requires special attention for maintenance or design updates while maintaining the philosophical aspects of the local culture. Therefore, this community service activity focuses on developing traditional lamin designs in the Pampang cultural village. The methods used are literacy assessment, drawing/design making, lecture/concept presentation, discussion, and evaluation. The results of this activity are in the form of products and services, working drawings and mockups of the redesign of traditional lamin buildings which are expected to contribute to the preservation of the original culture of East Kalimantan.